Outcomes of 3-D corrective osteotomies for paediatric malunited both-bone forearm fractures. (February 2022) - Roth, Kasper C.; van Es, Eline M.; Kraan, Gerald A.; Verhaar, Jan A. N.; Stockmans, Filip; Colaris, Joost W.
Closed treatment of paediatric diaphyseal forearm fractures carries the risk of re-displacement, which can lead to symptomatic malunions. This is because growth will not correct angulation deformity as it does in metaphyseal fractures. The purpose of this prospective cohort study was to evaluate the outcomes after 3-D-planned corrective osteotomy with patient-specific surgical guides for paediatric malunited forearm fractures causing impaired pro-supination. Our primary outcome measure was the gain in pro-supination at 12 months follow-up. Fifteen patients with a mean age at trauma of 9.6 years and time until osteotomy of 5.9 years were included. Preoperatively, patients displayed a mean pro-supination of 67° corresponding to 44% of the contralateral forearm. At final follow-up, this improved to 128°, achieving 85% of the contralateral side. Multivariate linear regression analysis revealed that predictors of greater functional gain after 3-D corrective osteotomy are severe preoperative impairment in pro-supination, shorter interval until 3-D corrective osteotomy and greater angulation of the radius. Level of evidence: III